Synthesis And Characterization Of Thermoresponsive Poly(N-Isoproylacrylamide)-DNA Bioconjugates - Ooi, Wei Yang (2012)
Bioconjugates (PNIPAAm−graft−DNA) of poly(N-isopropylacrylamide) (PNIPAAm) grafted with single-stranded (ss) DNA were synthesized via radical copolymerization. The bioconjugates self-assembled above its lower critical solution temperature (LCST) in aqueous solution to form micelle-like colloidal nanoparticles. When the ssDNA of the nanoparticle hybridizes with complementary DNA, the particles aggregate above a certain threshold of salt concentration with drastically increased turbidity in solution.